(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Purpose -The article presents indicators to measure the sustainable development of enterprises in terms of economy, society and environment; evaluates the correlations between effective factors such as ROE, ROA, PE, EPS, market capitalization and the disclosure of information on the sustainable development of enterprises. We aim to provide a theoretical basis for solving practical accounting-related problems in larger organizations and society. We also hope to complement the purely theoretical research on methods of assessing economic, social and environmental impacts. The article presents the essence of applied accounting research that is contextualized with relevant practical implications and contributes to the theoretical understanding towards sustainable development.